2021
DOI: 10.31674/mjn.2021.v12i03.003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Educational Intervention on Mothers' Knowledge, Attitude and Practice About Proper Antibiotic Use in a Selected Family Health Center

Abstract: Background: Improper antibiotic use is a significant community health issue that contributes to antibiotic resistance. Insufficient mothers' knowledge about the cautious antibiotics use in treating common childhood diseases can end in its misuse. Improving mothers' awareness about correct antibiotic use is the main aspect. The study is aimed to assess the effect of an educational intervention on mothers' knowledge, practice and attitude about proper antibiotic use. Methods: A quasi-experimental design -one gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
2
3
0
Order By: Relevance
“…Parents give the antibiotic to their children if it is not necessary to wait and a child with cold and heart symptoms will be sick for a longer period if not treated with antibiotics, underscoring the satisfactory improvement in practice when comparing pre-test and post-test. This result is similar with the previous result which found that overall practice's score of parents was unsatisfactory before implementing the educational program, with an improvement of the overall practice score after the implementation of the educational program (Abd El-Kader & Mohammed, 2021).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Parents give the antibiotic to their children if it is not necessary to wait and a child with cold and heart symptoms will be sick for a longer period if not treated with antibiotics, underscoring the satisfactory improvement in practice when comparing pre-test and post-test. This result is similar with the previous result which found that overall practice's score of parents was unsatisfactory before implementing the educational program, with an improvement of the overall practice score after the implementation of the educational program (Abd El-Kader & Mohammed, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…However, the knowledge and attitude of parents about using antibiotics is significantly improved through the educational program. This finding is consistent with studies that were conducted by Shehadeh et al (2016), andAbd El-Kader andMohammed (2021), who reported that the overall knowledge about appropriate antibiotic use improved educational intervention. Moreover, the present finding was in line with a community-based interventional study conducted in the United Arab Emirates by Rabbani et al (2020) using an awareness survey of the World Health Organization about antibiotic resistance.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Pediatric caregiverfocused education is effective at changing parent attitudes toward the use of antibiotics as shown in our study. A study conducted in Malaysia reveals that health education session on appropriate use of antibiotics improved mothers' level of awareness, practice and attitude about proper use of antibiotic of their children compared to baseline measures [15]. Similarly, in an intervention study using educational videotape on antibiotic use among parents in USA, the parents who were exposed to the videotape were significantly less inclined to seek antibiotics for viral infections than those not exposed [16].…”
Section: Discussionmentioning
confidence: 97%
“…Section one provided details of participants demographics, section two was a 10-item question on knowledge of antibiotics in treatment of infections and measures to reduce infection and use of antibiotics in pediatrics, while section three was an 8-item question on appropriate use of antibiotic in pediatric dosage form. Questions were developed from extensive literature review on similar studies that have been done [13][14][15]. Responses were presented in a 5-likert scale of strongly disagree, disagree, undecided, agree and strongly agree with a score of 1 to 5, respectively.…”
Section: Data Collectionmentioning
confidence: 99%